A Lakatosian Systematic Review of Realistic Mathematics Education Research (2020–2024) - Syifa Salsabila; Al Jupri; Prana Dwija Iswara; Anggi Umayrah; Syifa Fauziah (Universitas Sebelas Maret, 2026)
This literature review analyzes the historical development and theoretical frameworks proposed by key philosophers in Realistic Mathematics Education (RME). This study is important because recent RME research has largely focused on empirical implementation, leaving a theoretical gap in understanding how RME evolves as a scientific programme. A Scopus database search using the keyword “Realistic Mathematics Education” (conducted in March 2024) yielded 130 documents, from which 17 met the inclusion criteria for review. Using a descriptive and Lakatosian coding approach, each article was categorized into hard core, protective belt, theoretically progressive, and empirically progressive classifications, with double-coding applied to ensure reliability. The analysis results show that (1) most RME studies between 2020 and 2024 remain within the protective-belt category of Lakatos’ framework, focusing on confirming existing models; (2) a smaller number of studies demonstrate empirically progressive characteristics by introducing new context-based designs; and (3) two emerging topics—RME in Indonesian cultural contexts and RME based on Islamic values—represent the most progressive theoretical contributions. These findings imply that future RME research should move toward theoretical innovation and broaden its epistemological foundation beyond classroom implementation to strengthen its position as a developing scientific programme.